HIV prevalence among men who have sex with men, transgender women and cisgender male sex workers in sub-Saharan Africa: a systematic review and meta-analysis - Kloek, Mariëlle; Bulstra, Caroline A.; van Noord, Laura; Al-Hassany, Lina; Cowan, Frances M.; Hontelez, Jan (Journal of the International AIDS Society, 2022)
Developing effective targets, policies and services for key populations requires estimations of population sizes and HIV prevalence across countries and regions. We estimated the relative and absolute HIV prevalence among men who have sex with men (MSM), transgender women and men, and male and transgender sex workers (MSW and TGSW) in sub-Saharan African countries using peer-reviewed literature.
Gesehen am 17.01.2023